2021
DOI: 10.3389/fendo.2021.795111
|View full text |Cite
|
Sign up to set email alerts
|

Use of Thyroid Hormones in Hypothyroid and Euthyroid Patients: A 2020 THESIS Questionnaire Survey of Members of the Swedish Endocrine Society

Abstract: BackgroundThe standard treatment of hypothyroidism is levothyroxine (LT-4). However, there are several controversies regarding treatment of hypothyroid patients.AimTo investigate the Swedish endocrinologists’ use of thyroid hormones in hypothyroid and euthyroid individuals.MethodsPhysician members of the Swedish Endocrine Society (SEF) were invited by e-mail to participate in an online survey investigating this topic.ResultsOut of the eligible 411 members, 116 (28.2%) responded. The majority (98.9%) stated tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(44 citation statements)
references
References 49 publications
20
24
0
Order By: Relevance
“…This is the first survey on the use of TH by Belgian specialists. As elsewhere in Europe [ 12 20 ] and in agreement with international guidelines, the survey confirmed that LT4 is the treatment of choice for Belgian hypothyroid patients. However, a significant proportion of respondents also use TH for more controversial indications, such as infertile euthyroid TPOAb positive women and a growing benign goiter.…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…This is the first survey on the use of TH by Belgian specialists. As elsewhere in Europe [ 12 20 ] and in agreement with international guidelines, the survey confirmed that LT4 is the treatment of choice for Belgian hypothyroid patients. However, a significant proportion of respondents also use TH for more controversial indications, such as infertile euthyroid TPOAb positive women and a growing benign goiter.…”
Section: Discussionsupporting
confidence: 76%
“…However, a significant proportion of respondents also use TH for more controversial indications, such as infertile euthyroid TPOAb positive women and a growing benign goiter. A similar or even greater preference for the treatment of infertile euthyroid women in the presence of thyroid autoimmunity was reported by French (31.7%), Greek (31.9%), Romanian (36.4%), Italian (37.3%), Danish (42.1%), Swedish (47.3%), Spanish (48.5%) and Polish (63.4%) endocrinologists who responded to this question, respectively [ 12 20 ], although the limited available evidence does not support this approach. In the case of assisted reproductive technology, all large randomized controlled trials in this population concluded that there is no benefit from LT4 treatment [ 21 , 22 ], which was confirmed in the recent TABLET trial including euthyroid TPOAb positive women with a medical history of (recurrent) miscarriage or receiving treatment for infertility [ 23 ].…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations